The Shift from Print to Digital Media and Its Effect on Users' Media Literacy in Critiquing the Depth of News: A Systematic Literature Review - Meyka Septira Utami Pinem (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Since the global outbreak of coronavirus, the existence of print media has been displaced by online media which the public can easily access any information from their smartphones. However, with this change the credibility of online media is often questioned because of the rampant fake news circulating, where one of the reasons is accessibility that everyone could become a writer. On the other hand, the editing process is considered not as strict as the printed media, so that it has a stigma that this news is just faster than the others but without any appropriate confirmation of facts. Thus this systematic literature review study will discuss the effect of changing print media to digital media and its influence on user media literacy in criticizing news The results obtained show that there are still many people, especially the younger generation, who cannot distinguish fake news from the accurate one. In conclusion critical media literacy is needed so that journalism in the future does not experience setbacks.